EFEKTIVITAS PROGRAM KELUARGA HARAPAN DI KELURAHAN ANRONG APPAKA KABUPATEN PANGKEP - Kartini, Andi; Mustari, Nuryanti; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to describe and analyze government policies in the form of the Family Hope Program and to determine the effectiveness of this program in efforts to reduce poverty in the Anrong Appaka sub-district. The research design used is descriptive with a qualitative approach. The results of this study indicate that the Family Hope Program in efforts to reduce poverty in Anrong Appaka Village is less effective in terms of several aspects: Understanding Program, Right on Target, Timely, Goal Achievement and Real Change. 1) The PKH understanding program is carried out routinely every two times by the assistant by inviting KPM and related parties in the implementation of PKH. 2) The right target, there are community deviations that do not meet PKH criteria but are recorded as PKH assistance recipients. 3) Timely, the provision of assistance is not timely because the assistant's report to the center is sometimes delayed. 4) achieving the goal, PKH participants have received their rights in the form of cash assistance. 5) Real Change, PKH assistance has made a significant contribution to PKH participants and KPM feel helped by PKH assistance.